(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2014)
Desire is a product of evolution, and the emotional/motivational processes on which it is based are an essential adaptive resource for humans and animals. The development of the nervous system, the appearance of emotion and of the complex cognitive functions that accompany it are based on neurobehavioral endowments responsible for the preparation of behavioral plans guided by "attribution of value", that is motivation. And motivation, when associated to rewarding or negative experiences, implies the possibility to attribute incentive value to the object that is not linked, originally, to the satisfaction of needs.